Metacognitive Differences in Amnestic Mild Cognitive Impairment and Healthy Cognition: A Cross-Sectional Study Employing Online Measures - Grigoria Bampa; Magdalini Tsolaki; Despina Moraitou; Panagiota Metallidou; Elvira Masoura; Maria Mintziviri; Konstantinos Paparis; Dorothea Tsourou; Georgia Papantoniou; Maria Sofologi; Vasileios Papaliagkas; Georgios Kougioumtzis; et al. (Journal of Intelligence, 2023)
This study aimed to examine metacognitive abilities in individuals diagnosed with amnestic mild cognitive impairment (aMCI) by using online metacognitive measures during cognitive tasks. A total of 100 participants were enrolled, all aged 50 or older (mean age = 61.98; SD = 6.27), and with a minimum of six years of education (mean = 14.95; SD = 2.94). The sample included 50 individuals with aMCI (34 females) and 50 healthy controls (HC) (33 females). Both groups underwent metacognitive versions of memory tasks (Doors and People) and executive functions tasks (Wisconsin Card Sorting Test). Metacognition was assessed through confidence ratings given after each answer (referred to as metacognitive monitoring) and the accuracy of the participants’ decisions to include or exclude answers from their final scores (known as metacognitive control). The results showed that although individuals with aMCI were aware of their cognitive limitations—evidenced by their lower confidence ratings across all tasks—they still exhibited overconfidence relative to their actual performance. Moreover, they included a greater number of incorrect answers in their final scores compared to the healthy control group. These findings suggest that while individuals with aMCI retain some level of awareness, their self-evaluations appear to lack precision. This observation was consistent across both types of cognitive tasks. The results underscore the need for additional research to better understand metacognition in MCI as well as the interplay between metacognitive monitoring and control.